A thematic analysis of smokers' and non-smokers' accounts of E-cigarettes. (January 2022) - Wilson, Georgia Louise; Grogan, Sarah; Powell, Susan; Gee, Ivan; Porcellato, Lorna; Keenan, Joseph
This study explored smokers' and non-smokers' accounts of E-cigarettes. A total of 51 UK-based participants, 20 men and 31 women, responded to open-ended questions online. Inductive thematic analysis identified that the factors that influence E-cigarette behaviour and opinion in adult smokers and non-smokers are related to social context, informative sources, practical aspects and health implications. Participants presented varying accounts of E-cigarettes, suggesting that individual narratives regarding E-cigarettes are multi-faceted. This is important information for health professionals and policy makers tasked with advising on E-cigarette use.